SISTEM PENALARAN BERBASIS KASUS UNTUK MENDIAGNOSA KERUSAKAN KOMPUTER - Maulana Malik; Muh. Ihsan Sarita; La Ode Hasnuddin S. Sagala (Informatics Engineering Department of Halu Oleo University, 2016)
Case Based Reasoning is a method of reasoning with its main work system using a similarity measure. The basic idea of this system is that any possible problems are the same have the same solutions as well. The purpose of this study is to implement and test how accurate the Bayesian Theorem method for identifying cases of damage to the computer in case based reasoning system.Case based reasoning process consists of four stages namely retrieve, it means search and matching of the case; reuse, it means reuse of information and knowledge of the case; revise, it means revisiting the solution of the cases; and retain, it means saving the experience of new cases in the base case system.The system in this research will be built using Bayesian Theorem, modeling Unified Modeling Language (UML) and PHP programming languages with a MySQL database as a regulator of the system. Keywords— Case Based Reasoning, Bayesian Theorem, Computer Damage